Pemanfaatan Sumber Daya Alam untuk Meningkatkan Ekonomi Masyarakat di Desa Mulusan Gunungkidul - Ernaningsih, Zeny (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
The execution of village development research takes place in Mulusan Village, Gunung Kidul. There were 2 programs that we made: Village’s potential and utilization of natural resources. This research was carried out with the aim to develop villages in Gunung Kidul Regency, this was done to help improve the life quality of the village community from health and economic. This research activity was done by identifying the potential and problems that exist in the community, collecting data from the internet, then doing program design, followed by making ebooks and videos, after that they will be evaluated, then after all of the process are complete making the Final Report. The results from the village’s potential program are proposed programs such as the cultural carnival, jeep offroad area, dance groups, Ngeleng Cave and rice fields. Meanwhile, the utilization of natural resources contains tutorial about cooking healthy food and drink. Mulusan Village can be an attractive destination and has a lot of healthy and has a lot nutritious food ingredients for health.